The effects of psilocybin on cognitive and emotional functions in healthy participants: Results from a phase 1, randomised, placebo-controlled trial involving simultaneous psilocybin administration and preparation. (January 2022) - Rucker, James J; Marwood, Lindsey; Ajantaival, Riikka-Liisa J; Bird, Catherine; Eriksson, Hans; Harrison, John; Lennard-Jones, Molly; Mistry, Sunil; Saldarini, Francesco; Stansfield, Susan; Tai, Sara J; Williams, Sam; et al.
Background: Psilocybin, a psychoactive serotonin receptor partial agonist, has been reported to acutely reduce clinical symptoms of depressive disorders. Psilocybin's effects on cognitive function have not been widely or systematically studied. Aim: The aim of this study was to explore the safety of simultaneous administration of psilocybin to healthy participants in the largest randomised controlled trial of psilocybin to date. Primary and secondary endpoints assessed the short- and longer-term change in cognitive functioning, as assessed by a Cambridge Neuropsychological Test Automated Battery (CANTAB) Panel, and emotional processing scales. Safety was assessed via endpoints which included cognitive function, assessed by CANTAB global composite score, and treatment-emergent adverse event (TEAE) monitoring. Methods: In this phase 1, randomised, double-blind, placebo-controlled study, healthy participants ( n = 89; mean age 36.1 years; 41 females, 48 males) were randomised to receive a single oral dose of 10 or 25 mg psilocybin, or placebo, administered simultaneously to up to six participants, with one-to-one psychological support – each participant having an assigned, dedicated therapist available throughout the session. Results: In total, 511 TEAEs were reported, with a median duration of 1.0 day; 67% of all TEAEs started and resolved on the day of administration. There were no serious TEAEs, and none led to study withdrawal. There were no clinically relevant between-group differences in CANTAB global composite score, CANTAB cognitive domain scores, or emotional processing scale scores. Conclusions: These results indicate that 10 mg and 25 mg doses of psilocybin were generally well tolerated when given to up to six participants simultaneously and did not have any detrimental short- or long-term effects on cognitive functioning or emotional processing. Clinical Trial Registration: EudraCT (https://www.clinicaltrialsregister.eu/ ) number: 2018-000978-30.